A Mixed-Methods Study of Two Modes of the Circle of Security. (January 2022) - Sadowski, Christina; Goff, Rachel; Sawyer, Neroli
Purpose: This study compared the impact, challenges, and benefits of the Circle of Security-Parenting (COS-P) intervention across two delivery modes: group center-based (GCCOS-P) and individual home-based (IHCOS-P). Methods: This mixed-methods study compared the impact of the COS-P on parental reflective functioning and parental stress across two delivery modes: GCCOS-P ( n = 7) and IHCOS-P ( n = 7). It compared the challenges and benefits of each, from the qualitative perspectives of participants ( n = 2 IHCOS-P; n = 3 GCCOS-P) and facilitators ( n = 4). Results: Quantitative statistical analysis comparing pre- and postintervention measures suggest that each delivery mode was equally effective in reducing parental stress and generally noneffective with respect to parental reflective functioning. Challenges and benefits of each mode, inherent in the peer/shared learning environment of the GCOS-P and the individualized, flexible delivery of the IHCOS-P, were identified. Discussion: This study adds to knowledge about the widely utilized COS-P, highlighting challenges and benefits of two modes of delivery.